Effectiveness Of Group Counseling With The Thought Stopping Technique In Improving The Self-Confidence Of Students Who Are Victims Of Abusive Relationship - Sri Mullatifah Hanum; Ade Chita Putri Harahap (IJGIE (International Journal of Graduate of Islamic Education), 2025)
Students who are victims of abusive relationships tend to experience a decline in self-confidence due to prolonged emotional and psychological pressure. Low self-confidence can hinder their ability to make decisions, interact socially, and regulate emotions. This study aims to determine the effectiveness of group counseling using the thought stopping technique in improving the self-confidence of students affected by abusive relationships. The research used a quasi-experimental method with a non-equivalent control group design. The subjects were five students with low self-confidence levels. Data were collected using a self-confidence scale and analyzed with the Wilcoxon test. The results showed a significant increase in the experimental group after receiving group counseling with the thought stopping technique (significance value 0.043 < 0.05). Meanwhile, no change was found in the control group. Therefore, the thought stopping technique in group counseling is proven effective in increasing the self-confidence of students who are victims of abusive relationships.